Strategi Inlis Lite Dalam Meningkatkan Pelayanan E-Digital Library di Perpustakaan Pondok Pesantren Zainul Hasan Genggong - Fathorosi; Ni’mah, Mamluatun; Hayati, Nur (El-Idare, 2024)
In an era where information is the main thing, digital transformation is not only a necessity, but a necessity for institutions such as libraries. Genggong Library is one of the institutions that is trying to improve e-Digital Library services by adopting the Inlis Lite strategy. This research aims to explain the inlis lite strategy in improving e-digital library services at the Zainul Hasan Genggong Islamic Boarding School. The research uses a qualitative approach, with data collection through interviews with library heads and document analysis related to the implementation of Inlis Lite. The research results show that the use of Inlis Lite has made a significant contribution in improving operational efficiency, ease of navigation, cataloguing, book data collection, attendance and accessibility of digital collections in libraries.